2021
DOI: 10.37637/ab.v4i3.733
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ability Study for Grain Yield and Agronomic Traits of Quality Protein Maize (Zea mays L.) Inbred Lines Adapted to Mid-Altitude Agroecology of Ethiopia

Abstract: In spite of the importance of quality protein maize to alleviate protein deficiency, almost all maize varieties cultivated in Ethiopia are normal maize varieties, which are devoid of lysine and tryptophan. Perusing the combining ability of QPM inbred for grain yield and its components is vital to design appropriate breeding strategies for the development of nutritionally enhanced maize cultivars. A line x tester analysis involving 36 crosses generated by crossing 9  elite maize inbred lines with 4 testers were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…An F-test was conducted to study the effect of genotype. Analysis of Line x Tester used quantitative genetic analysis by SCA criteria as follows: (1) positive and high if SCA is positive and equals/ more than one of its standard error, (2) negative and high if SCA is negative and equals/more than one of its standard error, (3) positive and low if SCA is positive and less than once of its standard error, and (4) negative and low if SCA is negative and less than once of its standard error (Akula et al, 2016;Bhusal & Lal, 2020;Natol, 2017;Rani et al, 2018;Yadesa et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An F-test was conducted to study the effect of genotype. Analysis of Line x Tester used quantitative genetic analysis by SCA criteria as follows: (1) positive and high if SCA is positive and equals/ more than one of its standard error, (2) negative and high if SCA is negative and equals/more than one of its standard error, (3) positive and low if SCA is positive and less than once of its standard error, and (4) negative and low if SCA is negative and less than once of its standard error (Akula et al, 2016;Bhusal & Lal, 2020;Natol, 2017;Rani et al, 2018;Yadesa et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…General combining ability (GCA) relates to the parent and results from the additive gene's effect. Specific combining ability results from non-additive gene effects, such as dominance, epistasis, and the impact of genotype x environment (Sprague & Tatum, 1942;Yadesa et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researchers noted the significance of nonadditive gene action is responsible for grain production and other characteristics. However, the importance of additive gene action was reported by other researchers (Sedhom et al, 2021;and Yadesa et al, 2022).…”
Section: Introductionmentioning
confidence: 91%
“…However, the SCA value should be read according to the direction of selection of the observed traits [17]. Line combinations with significantly negative SCA values are the best for early flowering because they are associated with early maize maturity [22]. Positive and significant SCA values from the line combinations for flowering age traits indicated that this line combination was not good in terms of flowering age.…”
Section: General -Specific Combining Abilitymentioning
confidence: 99%